LM Tests for Random Effects - Greene, William; McKenzie (NYU Stern School of Business, 2012)
We explore practical methods of carrying out Lagrange Multiplier tests for variance components in two models in which the derivatives needed for the test are identically zero at the restricted estimates, the random effects probit model and the stochastic frontier model. The techniques are illustrated with two applications.